Collaboration Dynamics in Hajj Pilgrim Reception Services at Bekasi Hajj Dormitory 2024M 1445H - Anggraini, Dwi Isti; Pradita, Andre Rosi; Tanuwijaya, Frianka; Asropi, Asropi; Rahayu , Neneng Sri (JENTRE, 2025)
The Haji Ramah Lansia’s Theme remains in effect for Hajj activities in 1445 H / 2024M. The Decree General of PHU 185/2023 was issued to optimize services to pilgrims, particularly older pilgrims, by mandating one-stop services for pilgrim welcome. Various institutions, including the Office of the Ministry of Religion of West Java Province, Bandung Class I Health Quarantine Centre (BKK), immigration officers, the Bekasi Embarkation Hajj Dormitory UPT, and the Office of the Ministry of Religion of the Regency/City, must work together to implement these regulations. This study was carried out to investigate the dynamics of existing partnerships. According to the findings, collaborative dynamics began with a study conducted by the Head of the Hajj Dormitory Subdirectorate. Each unit has a distinct function in issuing SOPs, general guidelines, and technical guidelines from all PPIH fields. Both constructive dispute resolution and a comprehensive training system promote effective collaboration among parties.